2017
DOI: 10.1371/journal.pntd.0005297
|View full text |Cite
|
Sign up to set email alerts
|

Detection of a Potential New Bartonella Species “Candidatus Bartonella rondoniensis” in Human Biting Kissing Bugs (Reduviidae; Triatominae)

Abstract: BackgroundAmong the Reduviidae family, triatomines are giant blood-sucking bugs. They are well known in Central and South America where they transmit Trypanosoma cruzi to mammals, including humans, through their feces. This parasitic protozoan is the causative agent of Chagas disease, a major public health issue in endemic areas. Because of the medical and economic impact of Chagas disease, the presence of other arthropod-borne pathogens in triatomines was rarely investigated.Methodology/Principal findingsIn t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 28 publications
(17 citation statements)
references
References 40 publications
0
17
0
Order By: Relevance
“…Francisella in the Gulf Coast tick [75]). Others, like sheep keds (Melophagus ovinus [83]) and a single kissing bug species (Eratyrus mucronatus [84]), were found to carry Bartonella species of an unknown phenotype. In our data, Bartonella was the second most abundant taxa found in every life stage of T. rubida.…”
Section: Origin Of the Microbiome Bacteria: Inheritance Vs Environmentmentioning
confidence: 99%
“…Francisella in the Gulf Coast tick [75]). Others, like sheep keds (Melophagus ovinus [83]) and a single kissing bug species (Eratyrus mucronatus [84]), were found to carry Bartonella species of an unknown phenotype. In our data, Bartonella was the second most abundant taxa found in every life stage of T. rubida.…”
Section: Origin Of the Microbiome Bacteria: Inheritance Vs Environmentmentioning
confidence: 99%
“…B. ancashensis was first reported in 2013 isolated from the blood of 2 patients with Peruvian warts (56,85). Moreover, preliminary data have shown several new Bartonella species to have a close phylogenetic relationship with B. bacilliformis, such as in the case of the recently described "Candidatus Bartonella rondoniensis," which shares between 84 and 91% identity with B. bacilliformis (82). Although there are few studies on these species, B. rochalimae has been described to be present in fleas (86) and to be widely disseminated (87)(88)(89)(90).…”
Section: Bartonellaceaementioning
confidence: 99%
“…Currently, 35 species of Bartonella have been identified (http://www.bacterio.net/index .html) and have international standing in nomenclature, and other species have been proposed, several of which are classified as "Candidatus" species (80). New species of Bartonella continue to be discovered, but frequently only partial genetic data obtained by molecular analysis are available (81)(82)(83). B. rochalimae was reported in 2007 to have caused an Oroya fever-like disease in a traveler returning from Peru (57), and a retrospective study also identified this species in the blood of a Peruvian patient with Carrion's disease (84).…”
Section: Bartonellaceaementioning
confidence: 99%
See 2 more Smart Citations